New Approach to Mapping Regional Vulnerability in Controlling Tuberculosis Disease in Indonesia - Herawati, Maria Holly; Hermawan, Asep; Dasuki, Dasuki; Supratikta, Hadi; Asyary, Al; Khomarudin, M Rokhis; Priyatna, Muhammad; Raflizar, Raflizar; Kristina, Kristina; Pracoyo, Noer Endah; Bisara, Dina; Purnami, Cahya Tri; Suteja, Mentari Nur Farida; Bachtiar, Yusrial; Sukoco, Noor Edi Widya; Lasut, Doni (Kesmas, 2024)
Tuberculosis (TB) in Indonesia is still a health problem. The TB prevalence in Indonesia ranks second in the world after India in 2023. Regional factors, inadequate healthcare facilities, and limited resources (financial, human, and infrastructure) are challenges requiring innovation to help the government control TB. TB eradication efforts need to be made with a comprehensive and effective approach. One method used is to look at the vast territory of Indonesia, therefore, mapping the TB disease vulnerability is a highly recommended method. The use of a Geographic Information System is expected to help map the TB vulnerability areas in Indonesia. Given the existence of several epidemiological, socio-geographic, and environmental factors influencing TB, the question arises of how to map TB vulnerability areas in Indonesia. This study used a cross-sectional design, secondary data was collected from several sources, and a vulnerability analysis was performed by considering several socio-environmental epidemiological variables. Furthermore, after the analysis, the TB area vulnerability category would be obtained along with a map of TB vulnerability areas in Indonesia according to regional and district analysis units. This study produces a TB susceptibility index and map in Indonesia for the regions of Sumatra, Java-Bali, and other regions.